2002
DOI: 10.1074/jbc.m110513200
|View full text |Cite
|
Sign up to set email alerts
|

Host Chaperones Are Recruited in Membrane-bound Complexes byPlasmodium falciparum

Abstract: The ability of malarial parasite to deploy proteins at the surface of infected erythrocytes is well known. After their synthesis within the parasite, the cargo proteins are exported from the parasite and carried across the erythrocyte cytoplasm to be delivered at the erythrocyte surface. Our knowledge about the mechanisms involved in this complex trafficking path is limited. We have addressed the involvement of chaperones in traffic across erythrocyte cytoplasm. Our analyses of the chaperones available to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
74
0
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 90 publications
(78 citation statements)
references
References 46 publications
3
74
0
1
Order By: Relevance
“…Reagents and Antibodies-Antisera to PfHsp70 and PfHsp90 were generated against the recombinant COOH-terminal fragments of proteins in rabbit (18). DSP was obtained from Pierce.…”
Section: Methodsmentioning
confidence: 99%
“…Reagents and Antibodies-Antisera to PfHsp70 and PfHsp90 were generated against the recombinant COOH-terminal fragments of proteins in rabbit (18). DSP was obtained from Pierce.…”
Section: Methodsmentioning
confidence: 99%
“…As exported proteins need to cross several membranes to target to their final destinations, it is suggested that molecular chaperones, such as the heat shock protein 40-kDa (HSP40) family (also called DnaJ proteins), will be involved to help regulate protein transport (6,55,68). Traditionally, HSP40 proteins regulate the activity of HSP70 in a manner that facilitates the folding of proteins under both normal and stress response conditions (20,34,53,54,90).…”
mentioning
confidence: 99%
“…In addition, Banumathy et al observed that KAHRP cofractionated with host chaperones in knob-enriched fractions, and human Hsp70 could be released from these complexes by addition of ATP (24). Taken together, this might indicate that Hsp40s are specifically recruited in membrane-bound and detergent-resistant complexes, and they may exert a function in the assembly of knobs in infected red blood cells.…”
Section: Type IV Hsp40smentioning
confidence: 90%
“…We therefore have to assume that, if the exported plasmodial type II Hsp40s provide a similar function in the red blood cell cytoplasm, the interacting partner would have to be human Hsp70. Banumathy et al (24) reported human Hsp70 in the P. falciparum infected erythrocyte to be present in detergent-resistant membranes. However, direct proof of interaction between P. falciparum Hsp40s and human Hsp70 is currently missing.…”
Section: Type II Hsp40smentioning
confidence: 99%